Comparative Analysis of Cognitive Dysfunction in Chronic Kidney Disease Patients Undergoing Hemodialysis Versus Continuous Ambulatory Peritoneal Dialysis (CAPD) - Sagala, Ida Meita; Rifai, Achmad; Gunawan, Atma (Universitas Brawijaya, 2026)
Background: The increasing prevalence of impaired cognitive function in patients with chronic kidney disease (CKD) represents a significant global health concern. Hemodialysis (HD) and Continuous Ambulatory Peritoneal Dialysis (CAPD) are two commonly employed treatment modalities for CKD; however, their effects on cognitive function in this patient population require further investigation. Aim: To compare the impairment of cognitive function between patients with CKD undergoing HD and those undergoing CAPD. Methods: This study employed a cross-sectional design utilizing observational methods conducted at Dr. Saiful Anwar Hospital from August 2024 to January 2025, involving 139 patients with CKD, comprising 50 patients undergoing CAPD and 89 patients undergoing HD. Cognitive function was assessed using the Montreal Cognitive Assessment-Indonesian version (MoCA-INA). Results: The prevalence of cognitive impairment was found to be 28.9% in patients undergoing HD and 40% in patients undergoing CAPD. The results of the comparative analysis indicated a significant difference between the cognitive scores of the CAPD group and those of the HD group, with a p-value of 0.008. Based on the comparison test of the degree of cognitive impairment, no significant differences were found between the HD and CAPD groups in the mild cognitive impairment (p = 0.471), moderate cognitive impairment (p = 0.317), and severe cognitive impairment (p = 0.480). Conclusion: There was a significant difference in the cognitive impairment scores between the CAPD group and the HD group.